'The man who hated Britain' – the discursive construction of 'national unity' in the Daily Mail. Issue 2 (14th March 2016) - Stoegner, Karin; Wodak, Ruth
ABSTRACT: In 2013, the British right-wing tabloid Daily Mail triggered a fierce controversy, focused on antisemitism and patriotism/nationalism. It was sparked by the publication of an article on the British economist Ralph Miliband with the provocative headline 'The man who hated Britain'. The lead refers to Ed Miliband, then leader of the British Labour Party: 'Ed Miliband's pledge to bring back socialism is homage to his Marxist father. So what did Miliband Snr really believe in? The answer should disturb everyone who loves this country'. In this paper, we analyse how Ralph Miliband is discursively constructed as a dangerous 'Other' and subsequently politically instrumentalised in a campaign against his son, Ed Miliband. We focus on how a particular concept of national unity is constructed with reference to the stereotype of the 'disloyal, intellectual, international Jew'. This figure emerges as the 'Iudeus ex machina' in the scenario of impending doom in order, we assume, to distract attention from structural issues facing British society and economy. In our analysis we tackle the complex interdependencies of – mostly coded – antisemitic and nationalist rhetoric with the help of an interdisciplinary framework that integrates approaches to antisemitism, nationalism, media studies, and critical discourse studies, and related methodologies.